The journal ''Sobornyi razum'' as a source on the history of Renovationism in 1918 - Irina Vorontsova (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2021)
The next year 2022 marks the 100th anniversary of the Renovationist schism in the Russian Church. The question of whether post-revolutionary Renovationism was a continuation of the reform movement in the Russian Church at the beginning of the 20th century is still debated among historians, and this fact forces us to turn to poorly studied primary sources. One of sources is the journal Soborny Razum. Created in 1917 by the future leaders of the Renovationist schism, the All-Russian Union of Orthodox Democratic Clergy and Laity did not have its own press, and in 1918 the journal Soborny Razum began to be published on the basis of the Association of Spiritual Writers. It published articles by both the reformers of the beginning of the century and the post-revolutionary Renovationists, who in 1922 became the central fi gures of the Renovationist schism. In this journal, the principles of church renewal that belonged to the left-wing reformers of the early 20th century and remained relevant for the postrevolutionary renovationism were laid down. The article presents the results of a study of the issues of the journal for 1918 and off ers an answer to the questions: “whether reformism and post-revolutionary renovationism were one movement”, and “whether it is possible to agree that post-revolutionary renovationism is an exclusively political phenomenon”.